PSYCHOLOGICAL FEATURES OF THE PROGRAM OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE OF FUTURE SPECIALISTS - Олександренко, К. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article presents the results of the research of psychological features of the program of foreign language communicative competence of future specialists of international relations. The main task for foreign language teacher of training future specialists of international relations was to determine the creation of psycho-pedagogical conditions in which the future specialist can be realized as a subject of teaching and learning activities, is able to take an active personal position; it is possible to formate students' intrinsic motivation to achieve high rates of foreign language communicative competence; there are methods, forms and means of training aimed at developing future specialists professionally important qualities; management is organized a special cognitive activity of future specialists in order to reach the high figures in the study of a foreign language as at the scheduled training classes, and during self-training. A necessary condition for the development of an optimal level of foreign language communicative competence is the personality of the future specialist, his personal and professional resourses, and also specialized knowledge and skills, that are necessary for future activities. Key words: psychological features, application development, foreign language communicative competence, future specialists, international relations.